2017
DOI: 10.5603/gp.a2017.0022
|View full text |Cite
|
Sign up to set email alerts
|

The −2549 insertion/deletion polymorphism of VEGF gene associated with uterine leiomyoma susceptibility in women from Southeastern Iran

Abstract: Objectives: Vascular endothelial growth factor (VEGF) is an important angiogenic factor that regulates angiogenesis and mediates sex steroid-induced cell growth. The present study investigated the association of VEGF gene-2578C/A (rs699947) and −2549 insertion/deletion polymorphisms in the promoter region of VEGF-A gene and uterine leiomyoma susceptibility in Southeast of Iran. Material and methods:One hundred and fifty five women with uterine leiomyoma and 157 age, BMI, and ethnicity matched healthy women wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
3
1
Order By: Relevance
“… 44 The role of the VEGF −2549 polymorphism in uterine leiomyoma was investigated in the Iranian population in a previous investigation, whose results, similar to ours, demonstrated that the frequency of the I/I genotype was higher than that of the D/D genotype in the patient group than in the control group. 44 That study also proposed a higher risk of uterine leiomyoma in women carrying the I/I genotype compared with the D/D genotype. 44 The VEGF gene is involved in angiogenesis and tumor genesis in cancer.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“… 44 The role of the VEGF −2549 polymorphism in uterine leiomyoma was investigated in the Iranian population in a previous investigation, whose results, similar to ours, demonstrated that the frequency of the I/I genotype was higher than that of the D/D genotype in the patient group than in the control group. 44 That study also proposed a higher risk of uterine leiomyoma in women carrying the I/I genotype compared with the D/D genotype. 44 The VEGF gene is involved in angiogenesis and tumor genesis in cancer.…”
Section: Discussionsupporting
confidence: 75%
“… 44 That study also proposed a higher risk of uterine leiomyoma in women carrying the I/I genotype compared with the D/D genotype. 44 The VEGF gene is involved in angiogenesis and tumor genesis in cancer. 45 The frequency of the D/D genotype was higher in patients with breast cancer than in the control group, and the level of VEGF was higher in patients than in the control group in a prior study.…”
Section: Discussionmentioning
confidence: 94%
“…However, it is important to highlight that there are controversies regarding the potential of the D allele as a risk factor for clinical conditions, since a published study positively associated genotype II and/or allele I with pathologies such as uterine leiomyoma. 10 The increase in the frequency of smoking in the control group is not in accordance with a previous study 23 , in which women with PCOS showed higher frequency in relation to smoking, as well as a greater risk of worsening the metabolic profile. The increased frequency of family recurrence of PCOS in the study group is supported by the literature that evidences genetic factors in the etiology of this pathology, leading to a shared genetic predisposition.…”
Section: Discussioncontrasting
confidence: 58%
“…There may be more than two genotypes in the same gene locus, which is prevalent in areas with noncoding protein or without important adjustment functions in gene sequences. 18 The human VEGF gene is located on long arm of chromosome 6p21.3. The gene encoding VEGF is about 14 Kb in length and is composed of 8 exons and 7 introns alternately.…”
Section: Discussionmentioning
confidence: 99%